Biochemical and structural characterization of Streptococcus pyogenes C5a peptidase: a thesis presented in partial fulfillment of the requirements for the degree of Master of Science in Biochemistry at Massey University - Mouat, Pania Dawn (Massey University, 2002)
Streptococcus pyogenes, also known as Group A Streptococci, is a common causative agent of bacterial infections of the human upper respiratory tract, skin, and soft tissue. Non-suppurative sequelae of S. pyogenes infections include rheumatic fever, rheumatic heart disease, and acute glomerulonephritis. Recently there has been a resurgence of rheumatic fever and rheumatic heart disease as well as an increase in aggressive streptococcal disease such as toxic shock syndrome and necrotizing fasciitis. S. pyogenes produce a formidable array of virulence factors, one of which is C5a peptidase. The human complement factor C5a is a potent chemoattractant, macrophage activator, and an anaphylatoxin. The C5a peptidase of both Group A Streptococci and Group B Streptococci cleave C5a within its polymorphonuclear neutrophil binding site rendering it inactive. Mouse infection models have demonstrated a functional C5a peptidase assists colonization by retarding the infiltration of phagocytes to the foci of infection. C5a peptidase is a multidomain cell surface subtilisin-like serine protease (subtilase) with an Asp, His, and Ser catalytic triad. Comparative sequence analysis shows C5a peptidase has considerable sequence homology to Lactococcus lactis PrtP, both of which are highly specific endopeptidases. Whereas the subtilisins in general show broad substrate specificity profiles, the cell envelope proteinases of lactic acid bacteria demonstrate remarkable substrate specificity. The greater specificity of the cell envelope proteinases is held attributable to changes in variable regions within the structurally conserved regions and the presence of the A-domain, both of which have been demonstrated to modify specificity in PrtP proteinases. The aims of this project were to study the structural and biochemical properties of the C5a peptidase of Streptococcus pyogenes. C5a peptidase and variants were cloned, expressed, purified, and assayed for activity in under-agarose lymphocyte migration assays and in vitro digestion assays. Absence of activity was found in a C5a peptidase variant in which the A-domain was absent. Purified recombinant C5a peptidase and derivatives were screened for crystallization conditions. Crystallization conditions were found for recombinant C5a peptidase. To combat both the increasing incidence of S. pyogenes associated diseases, and increasing antibiotic resistance, new chemotherapeutic agents are required. This study was designed to elucidate the structural and biochemical basis of the substrate specificity of C5a peptidase, which will assist the design of potent inhibitors of this powerful virulence factor.
Keywords: Peptidase; Streptococcus pyogenes; Molecular genetics